Materials scarcity during the clean energy transition: Myths, challenges, and opportunities - Ku, Anthony Y.; Kocs, Elizabeth A.; Fujita, Yoshiko; Haddad, Andrew Z.; Gray, Robert W. (MRS energy & sustainability, 2024)
Efforts to reach net zero targets by the second half of the century will have profound materials supply implications. The anticipated scale and speed of the energy transition in both transportation and energy storage raises the question of whether we risk running out of the essential critical materials needed to enable this transition. Early projections suggest that disruptions are likely to occur in the short term for select critical materials, but at the same time these shortages provide a powerful incentive for the market to respond in a variety of ways before supply-level stress becomes dire. In April 2023, the MRS Focus on Sustainability subcommittee sponsored a panel discussion on the role of innovation in materials science and engineering in supporting supply chains for clean energy technologies. Drawing on examples from the panel discussion, this perspective examines the myth of materials scarcity, explains the compelling need for innovation in materials in helping supply chains dynamically adapt over time, and illustrates how the Materials Research Society is facilitating engagement with industry to support materials innovation, now and in the future. Graphical Abstract Highlights In this commentary, we examine the myth of materials scarcity, explain the compelling need for innovation in materials in helping supply chains dynamically adapt over time, and show how the materials research community can effectively engage with industry, policymakers, and funding agencies to drive the needed innovation in critical areas. Discussion Demand for certain materials used in clean energy technologies is forecasted to increase by multiples of current production over the next decades. This has drawn attention to supply chain risks and has created a myth that we will “run out” out of certain materials during the energy transition. The reality is that markets have multiple mechanisms to adapt over the long-term, and near-term shortages or expectations of shortages provide a powerful incentive for action. In this commentary, we highlight different ways materials innovation can help solve these issues in the near term and long term, and how the materials research community can effectively engage with industry and policymakers.